Building Igorot Identity: Examining the Improvisation and Anaphora in Selected Igorot Ethno Music of Salidummay Cultural Group, the Living Anitos and the Petune - Jonnelle D. Fagsao; Julie Grace M. Docallas; Christie Lynne C. Codod; Jennifer Ruth C. Tuazon; Delia A. Sumeg-Ang (Recent Trends in Arts and Social Studies Vol. 9, 2023)
Music serves as a key creative space for experimenting with creativity. It provides a means through which one can maintain the originality throughout time while also allowing for improvisation and variation. This paper examines the social and cultural context of Igorot music popularized by the Salidummay Cultural Group (SCG), the Petune (P), and the Living Anitos (TLA) in the Cordillera Administrative Region (CAR) of the northern Philippines, drawing on Drout’s (2006) work and hybrid identity anchored in Berger and Luckman’s (1966) Social Constructionism Theory (SCT) for its theoretical orientations and also the concept of rhetorical perspective through anaphoric repetitions. This paper tries to demonstrate how the chosen ethnic bands use [indigenous] music as a tool to navigate their Igorot positions through musical genres and approaches including improvisations and anaphoric tropes. The three ethnic bands chosen were accepted and loved as skilled and motivated artists descended from their Igorot ancestors, and it was also recognized that their cultural roots play an important role in developing their musical Igorot identities.